Prinsip Kehati-Hatian Bank Syariah Dalam Pelaksanaan Pembiayaan Murabahah Bi Al-Wakalah - Muhammad Ikhsan (Journal of Law and Administrative Science, 2023)
Abstract. Banking today is required to meet the needs of society, especially the needs of the Indonesian people who are predominantly Muslim who demand a banking system that is free from usury, so based on government regulation number 72 of 1992, sharia banks were established to accommodate the needs of the majority Muslim community, and many conventional banks are starting to form sharia banks. This article discusses how murabahah bi al-wakalah financing is implemented when viewed from the bank's prudential principles. This type of research is normative juridical research and uses a statutory approach and a conceptual approach. This article finds that the implementation of Murabahah bi al-wakalah financing at sharia banks does not comply with the principle of prudence because the power given to customers if there is no supervision of the process of implementing the contract that has been made with the bank, is very likely to be legally flawed due to abuse of power by the customer. So that Islamic banks in carrying out murabahah bi al-wakalah or murabahah financing do not fully comply with the bank's prudential principles.